Public Library Programs and Accommodations for Deaf and Hard-of-Hearing Children in the United States†. (28th December 2018) - Bushman, Bobbie; Fagan, Mary K
Abstract: In today's public libraries, children's librarians are challenged to provide inclusive programming that welcomes all individuals, including deaf and hard-of-hearing children at risk for delayed reading and literacy development. This study, using quantitative survey data and qualitative interview methods, investigated the programs and accommodations public libraries provide for deaf and hard-of-hearing children, the impetus for providing these programs, and the training required. Nearly 500 public libraries in the United States with service areas greater than 100, 000 patrons were invited to participate in an online survey. Fifty-nine librarians completed the survey and 11 participated in an additional telephone interview. Results indicated less than half of the libraries surveyed provided services for deaf and hard-of-hearing children. Nearly all of the programs offered were inclusive; among the accommodations provided were books with sign language and sign language interpreters. Training was the most common limitation facing librarians in their role as community partners in the literacy development of deaf and hard-of-hearing children.